Al-Ghazālī’s Perspective of Salam and Its Relevance to E-Commerce in Nigeria - Assayouti Jalaludeen Shuaib; Suraju Saheed Badmus (Universitas Muhammadiyah Yogyakarta, 2022)
The growth of the basic needs and wants of man takes place alongside man’sresponse to civilization. By way of economic civilization in Nigeria, the modeof the business transaction has had its extension stretched from onsite toonline, which has the internet space as its platform in a bid for globalization.There is no doubt that there is a plethora of anomalies; the obscurity ofintentions, excessive uncertainties -gharar, as well as day-light robbery fromboth ends of the buyers and sellers in the online business space. Thus, thispaper is aimed at examining the basic position of Islām on the businesstransaction in general, with a move to unraveling the prospects andchallenges of implementing salam on e-commerce, i.e., online business, asdiscussed by Imām Abū Ḥāmid Al-Ghazālī in his Iḥyā’u cUlūmi-d-Dīn. Themethodologies adopted are; descriptive, which enhanced adequatepresentation of the ways and manners online business is being operated, andanalytical, which aided the study in analyzing Al-Ghazālī’s views in relationto the Nigerian online business sphere. It was revealed that defrauding, themajor problem associated with e-commerce in Nigeria, is blamable on theparts of both the buyer and the seller. In order to curb the proliferation ofthis anomaly, the paper concluded by advocating the clarity of intentions andactivities as well as proper regulation and implementation of Islamicguidelines on salam on e-commerce, in line with Al-Ghazālī’s submission inhis Iḥyā’u cUlūmi-d-Dīn.